(untitled) (Revista Brasileira de Agroecologia, 2020)
Editores: Joel Donazzolo - Universidade Tecnológica Federal do Paraná – UTFPR, Dois Vizinhos – PR/Brasil. ORCID: https://orcid.org/0000-0002-6331-0378. E-mail: joel@utfpr.edu.br Flaviane Canavesi - Universidade de Brasília – UnB, Brasília – DF/Brasil. ORCID: https://orcid.org/0000-0003-1112-0633. E-mail: canavesiflaviane@gmail.com Editores de Seção: Daniela Sanches Frozi - Fundação Oswaldo Cruz, Brasília - DF/Brasil. ORCID: https://orcid.org/0000-0002-0324-1534. E-mail: danielafrozi@gmail.com Fernanda Savicki de Almeida - Fundação Oswaldo Cruz Pantanal, Campo Grande – MS/Brasil. ORCID: https://orcid.org/0000-0002-4840-9118. E-mail: fersavicki@gmail.com Fernando Ferreira Carneiro - Fundação Oswaldo Cruz Ceará, Eusébio - CE/Brasil ORCID: https://orcid.org/0000-0002-6625-9715 E-mail: fernandocarneirofiocruz@gmail.com Flávio Bezerra Barros - Universidade Federal do Pará, Belém – PA/Brasil. ORCID: https://orcid.org/0000-0002-6155-0511. E-mail: flaviobarros04@yahoo.com.br Islandia Bezerra - Universidade Federal de Alagoas, Maceio - AL/Brasil ORCID: https://orcid.org/0000-0002-0513-3545. E-mail: islandiabc@gmail.com Romier da Paixão Sousa - Instituto Federal do Pará, Castanhal - PA/Brasil, ORCID: https://orcid.org/0000-0002-2925-5408. E-mail: romier.sousa.ifpa@gmail.com Rumi Regina Kubo – Universidade Federal do Rio Grande do Sul, Porto Alegre – RS/Brasil. ORCID: https://orcid.org/0000-0002-2336-1402. E-mail: rumikubo2002@gmail.com